2010
DOI: 10.1172/jci40283
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of vasculogenesis, but not angiogenesis, prevents the recurrence of glioblastoma after irradiation in mice

Abstract: Despite the high doses of radiation delivered in the treatment of patients with glioblastoma multiforme (GBM), the tumors invariably recur within the irradiation field, resulting in a low cure rate. Understanding the mechanism of such recurrence is therefore important. Here we have shown in an intracranial GBM xenograft model that irradiation induces recruitment of bone marrow-derived cells (BMDCs) into the tumors, restoring the radiation-damaged vasculature by vasculogenesis and thereby allowing the growth of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

42
689
2
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 712 publications
(753 citation statements)
references
References 57 publications
42
689
2
6
Order By: Relevance
“…Angiogenesis is the subsequent process by which these vessels take shape from these existing blood vessels by 'sprouting' of endothelial cells thus expanding the vascular tree. 31,32 For tumour mass survival and continuous growth, tumours must develop a blood vessel network to help carry oxygenated blood, nutrients, etc. to the cancer cells within the tumour mass.…”
Section: Hs578ts(i) 8 -Exosomes Compared To Hs578t-exosomes Stimulatementioning
confidence: 99%
“…Angiogenesis is the subsequent process by which these vessels take shape from these existing blood vessels by 'sprouting' of endothelial cells thus expanding the vascular tree. 31,32 For tumour mass survival and continuous growth, tumours must develop a blood vessel network to help carry oxygenated blood, nutrients, etc. to the cancer cells within the tumour mass.…”
Section: Hs578ts(i) 8 -Exosomes Compared To Hs578t-exosomes Stimulatementioning
confidence: 99%
“…On the other hand, the relative abundance of immunosuppressive T‐regulatory cells (Tregs) (Bates et al., 2006; Pages et al., 2010) or CD4 + effector T‐cells (Denardo et al., 2011; Kohrt et al., 2005; Zhou et al., 2009) can be prognostic of comparatively poor outcome, as can the abundance of various myeloid cell types, including macrophages, neutrophils and immature myeloid cells (Qian and Pollard, 2010; Steidl et al., 2011; Zhou et al., 2009), a subset of which are referred to as myeloid‐derived suppressor cells on account of their ability to inhibit T‐cell functions (Sica and Bronte, 2007). Furthermore, studies in mouse models of cancer have revealed that profuse myeloid cell infiltration correlates with resistance to antiangiogenic therapies targeting the VEGF‐signaling axis (Bergers and Hanahan, 2008; Ferrara, 2010; Squadrito and De Palma, 2011), or accelerated tumor re‐growth following local tumor irradiation (Ahn and Brown, 2008; Kioi et al., 2010; Kozin et al., 2010). Additionally, there is considerable phenotypic and functional heterogeneity among macrophage and neutrophil subtypes, most simply reflected in the amalgam of conventionally or alternatively activated macrophages found in tumors, as well as in inflamed or healing tissues (Biswas and Mantovani, 2010; Coffelt et al., 2010; Gordon and Martinez, 2010; Nucera et al., 2011; Piccard et al., 2011).…”
Section: Variability and Dynamics Of Stromal Cell Componentsmentioning
confidence: 99%
“…In mice, radiotherapy-induced TAM infiltration is mainly attributed to radiation-induced hypoxia and the subsequent surge in hypoxia-regulated chemokines, such as CXCL12 [90,93]. Monocytes and macrophages expressing TIE2 -the receptor for Angiopoietins 1 and 2 -are highly receptive to increased hypoxia and CXCL12 levels [90,93,94], and TIE2-expressing monocytes/macrophages 10 have a profound ability to counteract hypoxia through the induction of angiogenesis [95].…”
Section: Innate Immune Cellsmentioning
confidence: 99%
“…In mice, radiotherapy-induced TAM infiltration is mainly attributed to radiation-induced hypoxia and the subsequent surge in hypoxia-regulated chemokines, such as CXCL12 [90,93]. Monocytes and macrophages expressing TIE2 -the receptor for Angiopoietins 1 and 2 -are highly receptive to increased hypoxia and CXCL12 levels [90,93,94], and TIE2-expressing monocytes/macrophages 10 have a profound ability to counteract hypoxia through the induction of angiogenesis [95]. As one may predict, neutralizing CXCL12 or blocking its receptor, CXCR4, to prevent TAM accumulation further delays tumor progression when combined with radiotherapy in orthotopic syngeneic and xenograft models of glioblastoma [90], as well as subcutaneous xenografts of lung carcinoma and syngeneic mammary tumors [93].…”
Section: Innate Immune Cellsmentioning
confidence: 99%
See 1 more Smart Citation